Pola Insurjensi Andi Azis sebagai Pemberontakan Militer dalam Pendekatan Model Keamanan Nasional - Novky Asmoro; Pujo Widodo; Resmanto Widodo Putro; Rizki Putri (LP4MK STKIP PGRI Lubuklinggau, 2022)
The Andi Azis incident gave an important meaning to the historical traces of the Indonesian military's struggle in eradicating the rebellion which was actually driven by its officers at that time. The incident that occurred in early April 1950 in Makassar, South Sulawesi was not only interpreted as a form of rebellion due to dissatisfaction with Jakarta's political policies in managing the formation of the state which at that time was still unstable but also as a social resistance of the regional army as the most effective representation of people's power in its time. Historical Research analysis which refers to the historical research methodology process in the form of Heuristics, Source Criticism, Interpretation, and Historiography in this article will try to juxtapose the theories of Insurgency and National Security so that the interesting dimensions of the Andi Azis incident bring new perspectives in the development of defense strategy studies and military philosophy. Andi Azis' rebellion movement can be a separate experience and lesson, especially for the Indonesian Armed Forces (Tni) in promoting a social approach and oneness with the community in addition to repressive measures in tackling similar movements, which are actually still happening in several regions in the archipelago.